2019
DOI: 10.15761/cdp.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathologic identification of circulating tumor cells (CTCs) in breast cancer: Application of size-based enrichment

Abstract: Circulating tumor cells (CTCs) are indicative of metastatic disease in multiple types of solid tumors. Technologic advances in CTC enrichment have yielded profound variability in both quantity and phenotypic characteristics of CTCs. While size-based exclusion methods have improved the sensitivity of CTC capture, their diminished specificity requires subsequent robust cytopathologic identification of CTCs. In this study, we compared CTC counts from Isolation by Size of Epithelial/Trophoblastic Tumor cells (ISET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Studies reported the feasibility of detection of CTCs using isolation by size-based Epithelial/Trophoblastic Tumor cells (ISET ® ) filters and stain by May–Grünwald–Giemsa in conjunction with identification criteria of nuclear irregularity, negative reactivity to immune cell marker as well as endothelial cell markers, and presentation of visible cytoplasm [ 26 ]. To test the negativity of CTC for CD31 in IF×3, we used the additional staining kit for DAPI/CK-FITC/CD31-PE/CD45-Cy5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported the feasibility of detection of CTCs using isolation by size-based Epithelial/Trophoblastic Tumor cells (ISET ® ) filters and stain by May–Grünwald–Giemsa in conjunction with identification criteria of nuclear irregularity, negative reactivity to immune cell marker as well as endothelial cell markers, and presentation of visible cytoplasm [ 26 ]. To test the negativity of CTC for CD31 in IF×3, we used the additional staining kit for DAPI/CK-FITC/CD31-PE/CD45-Cy5.…”
Section: Discussionmentioning
confidence: 99%
“…Our parallel double-detection format for CTC determination is efficient as it can be ready for pathological evaluation within the standard working hours of one day. The procedure is laboratory friendly and requires basic equipment and microscopes, and can be carried out with a standard grad-school laboratory setup compared with the FDA-approved CellSearch semi-automated CTC detection system or the CTC detection sensitivity of ISET [ 26 ] or using an immunomagnetic enrichment [ 25 ]. Hence, the method is cost-effective, and the cost of the consumables per 7.5 mL blood sample can be estimated at around $500 only.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this group also used immunofluorescent assay using immunofluorescent microscopy using A45-B/B3 and CD45 antibodies. Another method recently developed by Kamal et al utilizes a size-based exclusion principle for CTC enrichment which allows more sensitive capture of CTCs with minimal biological bias [31].…”
Section: Enrichment Isolation and Enumeration Of Circulating Tumor Cellsmentioning
confidence: 99%
“… 11 Probably for these reasons, data regarding basic CTC morphology in breast cancer are limited and thus the selection of the appropriate separation method is of outmost importance for proper cytopathological identification. 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…11 Probably for these reasons, data regarding basic CTC morphology in breast cancer are limited and thus the selection of the appropriate separation method is of outmost importance for proper cytopathological identification. [11][12][13][14] There are few published data how separation techniques affect CTCs morphology. [13][14][15][16] Therefore, we designed a study aimed to select the separation method that would allow the identification of CTCs based on their morphology that could be integrated in a routine cytopathology laboratory.…”
Section: Introductionmentioning
confidence: 99%